2008
DOI: 10.5194/bg-5-1215-2008
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater N<sub>2</sub>O emission factors of nitrate-contaminated aquifers as derived from denitrification progress and N<sub>2</sub>O accumulation

Abstract: Abstract.We investigated the dynamics of denitrification and nitrous oxide (N 2 O) accumulation in 4 nitrate (NO − 3 ) contaminated denitrifying sand and gravel aquifers of northern Germany (Fuhrberg, Sulingen, Thülsfelde and Göttingen) to quantify their potential N 2 O emission and to evaluate existing concepts of N 2 O emission factors. Excess N 2 -N 2 produced by denitrification -was determined by using the argon (Ar) concentration in groundwater as a natural inert tracer, assuming that this noble gas funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
71
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 41 publications
14
71
1
1
Order By: Relevance
“…These results are consistent with those of Weymann et al (2008) Kolle et al (1985) and Weymann et al (2010) postulated that high NO 3 --N removal in autotrophic denitrification zones was most likely caused by practically anoxic conditions and the presence of highly reactive microcrystalline pyrite. In the present study, the temporal variation of excess N 2 -N was low relative to site variability, with higher concentrations from July to October than at other times of the year.…”
Section: Groundwater Complete Denitrification: Excess N 2 -Nsupporting
confidence: 91%
See 4 more Smart Citations
“…These results are consistent with those of Weymann et al (2008) Kolle et al (1985) and Weymann et al (2010) postulated that high NO 3 --N removal in autotrophic denitrification zones was most likely caused by practically anoxic conditions and the presence of highly reactive microcrystalline pyrite. In the present study, the temporal variation of excess N 2 -N was low relative to site variability, with higher concentrations from July to October than at other times of the year.…”
Section: Groundwater Complete Denitrification: Excess N 2 -Nsupporting
confidence: 91%
“…Excess N 2 -N concentrations in our study sites were lower than those reported by Weymann et al (2008). Maximum values in the present study were between 5.60 -8.69 mg N L -1 at the L1 and L2 sites and were associated with high RP values (between 0.97 -0.99) at the interface and bedrock zones.…”
Section: Groundwater Complete Denitrification: Excess N 2 -Ncontrasting
confidence: 74%
See 3 more Smart Citations